Utilization of Wood Waste Mahang (Macaranga sp.) From Sawmill Industry For Making Wood Vinegar - Sutrisno, Lis; Sulaeman, Rudianda; Sribudiani, Evi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
ABSTRACT Wood vinegar is the result of condensation and combustion products directly or indirectly. One of the methodes to make wood vinegar is by condensing the smoke products of incomplete combustion (pyrolysis). Materials used for the manufacture of wood vinegar is mahang wood waste from the sawmill industry in the form of sawdust, shavings and slashes. This study aims to determine how much rendement, chemical constituents of Â woodÂ  vinegar (phenol, total acid and pH) as well as the colors of the various forms of raw materials. This experiment was carried out using a completely randomited design (CRD) consist of 3 treatments and 5 replications with parameters analyzed were rendement, chemical content and color wood vinegar produced. These results indicate that the form of raw materials affect rendement, chemical content, and color. Sawdust (C1) rendement yield of 14.66 %, phenol content of 15,48 mg/l, total acid of 5,08 %, pH of 2,1 and color of wood vinegar is yellow light brown. Chips (C2) rendement yield of 20,67 %, phenol content of 18,61 mg/l, total acid of 5,78 %, pH of 2,0 and color of wood vinegar is yellow brown. Slashes (C3) rendement yield of 38,98 %, phenol content of 18,80 mg/l, amount 7,72 % total acid, pH of 1,9 and color of wood vinegar is yellow dark brown. Recommended for more efficient utilization of wood waste mahang (Macaranga sp.). As materials are shaped blade of wood vinegar, because it has the highest rendement and good quality wood vinegar. Keywords: Wood Vinegar, Waste, Wood Mahang, Rendement.